2005
DOI: 10.1302/0301-620x.87b5.15427
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty with a sliding iliac graft for acetabular dysplasia

Abstract: We describe a new technique of reconstruction of the deficient acetabulum in cementless total hip arthroplasty. The outer iliac table just above the deficient acetabulum is osteotomised and slid downwards. We have termed this an iliac sliding graft. Between October 1997 and November 2001, cementless total hip arthroplasty with an iliac sliding graft was performed on 19 patients (19 hips) with acetabular dysplasia. The mean follow-up was 3.4 years (2 to 6). The mean pre-operative Harris hip score was 45.1 which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The complication rate in our series is comparable with that reported in other studies of THA for dysplastic hips [17][18][19][20][21][22][23]. Limb length discrepancy is one of the main problems in severely dysplastic hip replacement, since functional lengthening is limited by tight soft tissues, especially by the sciatic nerve.…”
Section: Discussionsupporting
confidence: 85%
“…The complication rate in our series is comparable with that reported in other studies of THA for dysplastic hips [17][18][19][20][21][22][23]. Limb length discrepancy is one of the main problems in severely dysplastic hip replacement, since functional lengthening is limited by tight soft tissues, especially by the sciatic nerve.…”
Section: Discussionsupporting
confidence: 85%
“…Some of these methods include proximally placed small acetabular cups, placement of the cup by penetration of the medial wall (medial protrusion technique), iliac bone sliding grafting, and lateral bulk grafting using an autograft or an allograft. [5][6][7]12,[17][18][19][20] In our technique; first, we found the true acetabulum, which is very important regarding biomechanics, and then we decorticated the defect in the superolateral acetabulum until the cancellous bone was reached. We cut the femoral head in two, determined the location of the graft, and held it in the smallest volume with enough graft size; thus eliminating large volume graft problems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have reported that graft stability and graft-bone contact are two of the most critical factors for graft incorporation. [2,9,10,20] In the original description by Harris, [2] the femoral head is curved to fit the ilium, and a notch is made in the ilium where the femoral head is placed. Subsequently, other authors have proposed cutting the femoral head to provide cancellous bone contact.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important aspects is the reconstruction of the supero-lateral defect of the acetabulum. [1][2][3][4][5] During the development of the Intraosseal Structural Graft (ISG) technique our research group also worked on the surgical instruments required during the operation. During the procedure in the cranial quadrant of the acetabulum a proximally hinged cortico-spongious plate is fashioned that is opened laterally and a wedge shaped graft made from the femoral head is impacted.…”
Section: Introductionmentioning
confidence: 99%